The Effect of DAR, CR, ROA and Corporate Governance Mechanism on Financial Distress in BUMN Companies Go Public on Bei Year 2016-2020 - Mesrawati, Mesrawati; Selly, Selly; Sherlytan, Stefanie; Natalia Sinaga, Meliana; Apryani Saragih, Rosella (Journal Research of Social Science, Economics, and Management, 2022)
Financial distress is a condition of financial difficulties experienced by the company in dealing with its finances. Problems Financial conditions that are not immediately resolved will lead to bankruptcy. Financial difficulties can start from liquidity difficulties (short term), as the lightest sign of financial distress, the worst is bankruptcy. Usually, when examining possible financial difficulties, a financial indicator model is used. These financial indicators are obtained through analysis of financial ratios contained in the company’s financial statement information. So This study aims to find out whether there is an effect of Debt To Asset Ratio, Current Ratio, Return On Asset and audit committee on financial distress in BUMN companies that go public on the IDX in 2016-2020 with multiple linear regression data analysis techniques. The population of state-owned companies is 20, selected using purposive sampling so that a sample of 13 companies is obtained with a total of 65 data. Statistic analysis used on this study are classic asumption test, normality test, heteroscedasticity test, multiple linear regression, Hypothesis testing using T-test, F-test and determinant coefficient analysis. The test results show that partially Debt To Asset Ratio and the audit committee have a significant negative effect on financial distress, partially Return On Asset has a positive effect on financial distress while the Current Ratio has no effect on financial distress. Simultaneous test results show that Debt To Asset Ratio, Current Ratio, Return on asset and the audit committee affect financial distress. We provide input suggestions to State-owned companies are expected to pay attention to their financial performance by taking into account the suitability of the level of debt used, the level of liquidity, the return on investment on their assets and the need for the number of members of the audit committee.